Empowering BUPDA Reform Access in The Management of Village Land Assets in Sesetan Village - UTAMA, I Wayan Kartika Jaya; WIRYANI, Made; ARTANAYA, Wayan; SUARJANA, I Wayan; PUTRA, I Made Aditya Mantara (Indonesia Strategic Sustainability, 2024)
This research was preceded by the aim of identifying and analyzing access to BUPDA reform for the empowerment of village land asset management in Sesetan village for the formation of customary BUPDA (BUPDA) so that it can prosper its krama Potential has not been optimally utilized for funds to support Tri Hita Karana activities in Indigenous Villages. The professionalism of human resources has not been optimal for managing potential. It was identified that there was a need for funds for indigenous villages to preserve customs and culture based on the teachings of Hinduism, which had increased, not optimally managing the potential of palemahan professionally for their welfare. The needs analysis aims to overcome problems in the empowerment of the Sesetan indigenous village for interest and overcome unemployment by implementing modern management with the establishment of business units and the appointment of pedalling as well as the application of information and communication technology as a medium of communication with stakeholders. The empowerment of indigenous villages will be achieved if participation and a shared commitment to make changes for the better. Potential is empowered through education and human resources training as an element driving the change.